Multidisciplinary approach in the treatment of cervical-cervical and cervical pregnancies with the use of modern low-invasive x-ray endovascular technology - A. E. Mitichkin; Yu. E. Dobrokhotova; S. V. Apresyan; D. G. Gromov; V. I. Dimitrova; S. A. Papoyan; S. A. Khlynova; A. G. Ishevsky; O. A. Slyusareva; V. A. Zametaev (Медицинский совет, 2018)
Multidisciplinary approach in the treatment cervical ectopic pregnancy has been developed, it includes the systemic use of methotrexate, the embolization of uterine arteries and follow-up fetal egg remove. The new method of combination treatment of cervical pregnancy of one-stage use of embolization uterine artery and temporary balloon occlusion of the internal iliac arteries was applied for the first time in Russia. This algorithm helps to preserve the reproductive function of women.